1986
DOI: 10.1073/pnas.83.16.6184
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive behavior induces release of nerve growth factor from mouse salivary gland into the bloodstream.

Abstract: Intraspecific fighting induced by 6-8 weeks of social isolation results in massive release of nerve growth factor (NGF) into the bloodstream of adult male mice. The amount of circulating NGF is highly correlated with the number of fighting episodes. Biological, radioimmunological, immunohistochemical, and ultrastructural studies show that NGF is discharged from the salivary gland into the blood within minutes after fighting and reaches the highest level 3-4 hr later. Adrenergic innervation of the salivary glan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
83
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(88 citation statements)
references
References 26 publications
5
83
0
Order By: Relevance
“…This may be due to the much higher number of fighting episodes that occurs as a result of isolation. Fighting induced a large increase in biologically active NGF in serum from isolated mice, when compared with the isolated nonfighting group, in agreement with previous results (22). The neurite outgrowth induced by both serum and hypothalamic extracts from chicken dorsal root ganglia and rat SCG was completely inhibited by NGF antibodies.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…This may be due to the much higher number of fighting episodes that occurs as a result of isolation. Fighting induced a large increase in biologically active NGF in serum from isolated mice, when compared with the isolated nonfighting group, in agreement with previous results (22). The neurite outgrowth induced by both serum and hypothalamic extracts from chicken dorsal root ganglia and rat SCG was completely inhibited by NGF antibodies.…”
Section: Resultssupporting
confidence: 81%
“…' , ._ P-< DISCUSSION Previous studies (22) showed that intraspecific fighting induced by social isolation results in a massive release of biologically active NGF from the submaxillary gland of adult male mice into the bloodstream and that the amount of circulating NGF is highly correlated with the number of fighting episodes. In this report we show that the same experimental paradigm leads also to a marked increase in NGF mRNA in the hypothalamus.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Aggressive behavior in male mice results in the release into the blood of large amounts of submaxillary NGF and renin (4,5), providing some evidence that these molecules play a physiological role. But surprisingly, these proteins are not detected in the SMG of related species.…”
Section: Introductionmentioning
confidence: 99%
“…9 -10). NGF accelerates the rate of wound healing in mice (11) and is released into the bloodstream of male mice from the salivary gland after fighting (12).…”
mentioning
confidence: 99%